ADMINISTRATIVE SANCTIONS FOR DRIVING UNDER THE ALCOHOL INFLUENCE - Zīle, Jana (Administrative and Criminal Justice, 2016)
The relative indicators of road traffic safety in Latvia are still amongst the worst in the EU Member States, despite the fact that the road safety level improvement rate in Latvia is one of the best in the European Union. Despite the reduction of severity of road accidents, it is still higher than the best national figures of EU. The publication examines the sanctions for driving under the influence of alcohol or narcotic or other intoxicating substances and their impact on traffic safety in Latvia, court statistics is analysed. The authors also provide their proposals for improving the situation.